2012
DOI: 10.1172/jci64151
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs contribute to compensatory β cell expansion during pregnancy and obesity

Abstract: Pregnancy and obesity are frequently associated with diminished insulin sensitivity, which is normally compensated for by an expansion of the functional β cell mass that prevents chronic hyperglycemia and development of diabetes mellitus. The molecular basis underlying compensatory β cell mass expansion is largely unknown. We found in rodents that β cell mass expansion during pregnancy and obesity is associated with changes in the expression of several islet microRNAs, including miR-338-3p. In isolated pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
168
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 157 publications
(182 citation statements)
references
References 77 publications
(95 reference statements)
8
168
1
2
Order By: Relevance
“…The expression of several miRNAs is affected by prolonged exposure to elevated concentrations of glucose, NEFA and proinflammatory cytokines [90]. Moreover, alterations in the expression of several islet miRNAs have been reported in different models of diabetes [91,92]. As recently proposed by Nesca et al [93], obesity and insulin resistance trigger changes in the levels of miR-132, miR-184 and miR-338-3p, which promote beta cell mass compensation.…”
Section: Contributors To Maintenance Of Islet Cell Mass In Adult Rodentsmentioning
confidence: 94%
“…The expression of several miRNAs is affected by prolonged exposure to elevated concentrations of glucose, NEFA and proinflammatory cytokines [90]. Moreover, alterations in the expression of several islet miRNAs have been reported in different models of diabetes [91,92]. As recently proposed by Nesca et al [93], obesity and insulin resistance trigger changes in the levels of miR-132, miR-184 and miR-338-3p, which promote beta cell mass compensation.…”
Section: Contributors To Maintenance Of Islet Cell Mass In Adult Rodentsmentioning
confidence: 94%
“…The expression of several miRNAs is affected by prolonged exposure to elevated concentrations of glucose, NEFA and proinflammatory cytokines [4]. Moreover, alterations in the levels of many islet miRNAs have been reported in different models of diabetes [5][6][7][8][9]. However, the functional impact of these miRNA expression changes and their potential role in the development of diabetes were, in most cases, not explored.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…A list of the microRNAs identified by these studies is provided in Table 2. Interestingly, a group of microRNAs including miR-34a, miR-132, miR-184, miR-199a-5p, miR-210, miR-212, miR-338-3p and miR-383 was found to be deregulated in different animal models of type 2 diabetes by independent research groups, and changes in their expression were confirmed by real-time PCR quantification [20,21,[29][30][31]. The functional role of some of these microRNAs in the regulation of beta cell function has been investigated in detail.…”
Section: Inappropriate Islet Microrna Expression As a Potential Causementioning
confidence: 98%
“…However, not all the changes in microRNA levels detected in the islets of diabetic animals have deleterious effects on beta cell activities. Indeed, reduction of miR-184 and miR-338-3p or a rise of miR-132 was found to trigger beta cell proliferation and improve survival and/or insulin release [20,21,31,33]. This suggests that these changes contribute to physiological processes that attempt to compensate for insulin resistance rather than to pathological events causing the appearance of diabetes.…”
Section: Inappropriate Islet Microrna Expression As a Potential Causementioning
confidence: 99%
See 1 more Smart Citation